Neurological Paraneoplastic Syndromes in most Common Cancers in Poland - Piątkiewicz, Julia; Krzyżanowska, Maria; Głogowska, Karen; Wojtas, Mikołaj; Sztybór, Mateusz; Maleszewska, Monika; Żmijewska, Aleksandra; Nowak, Gabriela; Kapica, Marcin; Kopacz, Wojciech (Journal of Education, Health and Sport, 2024)
INTRODUCTION: Paraneoplastic Neurological Syndromes (PNS) represent a heterogeneous group of diseases associated with the presence of neoplasm. The appearance of PNS can precede cancer diagnosis. The estimated frequency amongst cancer patients is about 1%. Malignant tumors represent a serious health problem and are the second leading cause of death in Poland. The aim of this study is to collect information about PNS focusing on cancers mostly diagnosed in Polish adults. REVIEW METHODS: The analysis was conducted based on information regarding PNS gathered from PubMed and Google Scholar within the context of selected cancers. THE STATE OF KNOWLEDGE: PNS develop from an autoimmune reaction in which onconeural antibodies are produced. The recent classification divides PNS to high risk, indicating a likely paraneoplastic origin and intermediate risk, if this association is less evident. Diagnosis is difficult and usually relies on exclusion methods. The symptoms described are non-specific and the diagnostic process may require the involvement of various specialists. The main approaches include cancer treatment, especially tumor removal and immunotherapy, which in certain may prove to be effective. SUMMARY: Although PNS is relatively rare, its detectability has recently increased. Many syndromes are especially associated with lung cancer (mainly small cell carcinoma). Breast and prostate cancers have also shown associations with certain syndromes. They can present with nonspecific symptoms related to different organ systems. Awareness and understanding of this phenomenon can be helpful amongst many specialists.